(untitled) (Indian Journal of Animal Production and Management, 2013)
The present study was conducted in the Dang district of Gujarat. Total 150 respondents were interviewed for the questionnaire prepared about scientific animal husbandry practices followed by them and constraints in adoption of those practices. The findings indicated that majority of farmers were following good breeding practices, but there is a problem of availability of timely A.I. facility in interior area. Farmers were much aware about clean milk production also, and that may be because of regular awareness programs run by dairy cooperative and government. Though, they were not following regular grooming practices. Crossbred cattle owners were not following regular hoof trimming, disbudding and ecto-parasite control practice. Because of unavailability of timely vaccination, schedule of vaccination was also not followed properly. Moreover this, farmers felt too high prices of concentrate mixture.